HUBUNGAN CAREER ADAPTABILITY DENGAN PERCEIVED FUTURE EMPLOYABILITY PADA MAHASISWA DI JAKARTA - Putri, Daniela; Gunawan, William (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
The increasingly competitive dynamics of the global labor market, driven by globalization and digitalization, require university graduates to develop high adaptability to face career challenges. This study aims to examine the relationship between career adaptability and perceived future employability among university students in Jakarta. The study employed a quantitative correlational approach with purposive sampling, involving 390 students aged 18–29 from various universities in Jakarta. The instruments used were the Career Adapt-Ability Scale-Short Form (CAAS-SF) and the Perceived Future Employability Scale (PFES). The validity test results showed that CAAS-SF items had coefficients ranging from 0.419 to 0.751 and PFES from 0.501 to 0.789, all above the acceptable threshold of r > 0.30. Reliability analysis showed high internal consistency (CAAS-SF: ? = 0.874; PFES: ? = 0.947). Spearman correlation analysis revealed a significant positive relationship between career adaptability and perceived future employability (r = 0.691; p < 0.001). These findings suggest that the higher the level of career adaptability among students, the more positive their perceptions of future employment prospects. ABSTRAKDinamika dunia kerja yang semakin kompleks akibat globalisasi dan digitalisasi menuntut lulusan perguruan tinggi memiliki kesiapan tinggi dalam menghadapi tantangan karier. Salah satu kompetensi penting yang perlu dimiliki mahasiswa adalah kemampuan untuk beradaptasi dalam karier atau career adaptability. Penelitian ini bertujuan untuk mengkaji hubungan antara career adaptability dengan perceived future employability pada mahasiswa di Jakarta. Penelitian ini menggunakan pendekatan kuantitatif korelasional dengan teknik purposive sampling dan melibatkan 390 mahasiswa berusia 18–29 tahun. Instrumen yang digunakan adalah Career Adapt-Ability Scale-Short Form (CAAS-SF) dan Perceived Future Employability Scale (PFES). Hasil uji validitas menunjukkan bahwa item-item pada CAAS-SF memiliki nilai koefisien antara 0,419 hingga 0,751 dan PFES antara 0,501 hingga 0,789, dengan reliabilitas tinggi (CAAS-SF: ? = 0,874; PFES: ? = 0,947). Hasil uji korelasi Spearman menunjukkan adanya hubungan positif yang signifikan antara career adaptability dan perceived future employability (r = 0,691; p < 0,001). Temuan ini menekankan pentingnya pengembangan career adaptability di kalangan mahasiswa sebagai upaya untuk meningkatkan kesiapan mereka dalam menghadapi dunia kerja masa depan.